Évangélismes croisés. Réforme épiscopale, renouveau spirituel et construction des frontières religieuses en France et en Italie au xvie siècle - Guillaume Alonge (Chrétiens et Sociétés, 2018)
The article focuses on the church reform movement that developed in the first half of the sixteenth century in Europe and was called Evangelism. It is a vast field of behaviors that was that of a consistent part of the Catholic hierarchies and many humanists of the time, convinced of the need for a radical reform of religious life rooted in the role of bishops, rather than popes, but faithful to a non-schismatic idea of ​​the Church. The focus is on two Catholic bishops – the Genoese Federico Fregoso and the Veronese Ludovico di Canossa – both involved in reform efforts and at the center of spiritual and political networks halfway between France and Italy, between the more conservative Catholicism and the tolerant Reformation of some humanists.